A decision framework to integrate in-situ and ex-situ management for species in the European Union - Staerk, Johanna; Colchero, Fernando; Kenney, Melissa A.; Wilson, Kerrie A.; Foden, Wendy B.; Carr, Jamie A.; Pereboom, Zjef; Bland, Lucie; Flesness, Nate; Martin, Tara; Maiorano, Luigi; Fa, Julia E.; et al. (Frontiers in Conservation Science, 2024)
Zoos and aquaria in the European Union (EU) can play a crucial role in the conservation of EU species, as they currently hold nearly half (49%) of EU terrestrial vertebrates. In this study, we analyzed the species composition and population sizes of EU zoos and developed a framework to prioritize recommendations for additional ex-situ and in-situ interventions for 277 at-risk EU species. Our results showed that EU zoos currently hold 39% of threatened EU species, 27% of EU endemic species, 62% of EU species vulnerable to climate change, 20% of EU species listed by the Alliance for Zero Extinction (AZE), 25% of Evolutionary Distinct and Globally Endangered (EDGE) EU species, while only 5% are subject to ex-situ conservation. Using our framework, we found that additional captive breeding was recommended for 60-61%% of species while expanding protected areas was recommended for only 2-22%, as 217 out of 277 species already met habitat protection targets. Both interventions were recommended for up to 20% of species, while the remaining 18% required no interventions because captive populations and habitat protection fully met targets. Our flexible framework can support more effective integrated conservation planning decisions for EU species and help identify target species for further in-depth assessment by the IUCN Ex-situ guidelines.